Fluoride Removal by Calcium-aluminum-cerium Ternary Composite: Adsorption Performances and Mechanism - Yuqiu LIU; Zihang GAO; Hui ZHOU; Yongkui ZHANG; Yabo WANG (Kuangchan zonghe liyong, 2025)
Fluoride-containing industrial wastewater poses great threat to environmental safety and human health. In this study, calcium-aluminum-cerium ternary composite (CAC) was synthesized by co-precipitation method, and characterized by XRD, FTIR, N2 adsorption, SEM, etc.. The performances and mechanisms of F- adsorption by CAC were thoroughly investigated. Experimental results showed that weakly acidic environment (pH 5.0) was favorable for F- removal by CAC adsorption. F- adsorption by CAC was a spontaneous and endothermic process, which could be well described by the Langmuir model. The maximum adsorption capacity was calculated to be 56.28 mg/g, while the adsorption equilibrium reached at about 12 h. The pseudo-second-order kinetic model fitted the adsorption kinetic well. F- adsorption was remarkably affected by the co-existing CO32- and HCO3-, while Cl-, Br-, SO42- influenced F- adsorption little. Electrostatic attraction and ion exchange were considered to be the main adsorption mechanisms.